2017
DOI: 10.1016/j.egypro.2017.08.198
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of a micro CHP system based on high temperature PEM fuel cells subjected to degradation

Abstract: Micro Combined Heat and Power (microCHP) systems based on High Temperature Polymer Electrolyte Membrane (HTPEM) fuel cells is a promising technology allowing to produce electricity and heat with very high efficiency and low emissions also for small power systems. Polybenzimidazole (PBI) based HTPEM fuel cells, thanks to their high CO tolerance, allow the use of fuels other than pure hydrogen by means of a simplified fuel processing unit. However, their relatively low performance and performance degradation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…High temperature polymer exchange membrane fuel cells (HT-PEM FC) have entered the market in the last decade [1]. This type of FC is considered as a clean and efficient power source for portable and stationary applications such as combined heat and power (CHP) application, stand-alone power, backup power and uninterrupted power supply (UPS) [2][3][4][5][6]. In HT-PEM FC a polybenzimidazole (PBI) membrane doped with phosphoric acid is used.…”
Section: Introductionmentioning
confidence: 99%
“…High temperature polymer exchange membrane fuel cells (HT-PEM FC) have entered the market in the last decade [1]. This type of FC is considered as a clean and efficient power source for portable and stationary applications such as combined heat and power (CHP) application, stand-alone power, backup power and uninterrupted power supply (UPS) [2][3][4][5][6]. In HT-PEM FC a polybenzimidazole (PBI) membrane doped with phosphoric acid is used.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that electrical, thermal, and co-generation efficiencies of 42.8%, 47.2% and 90% can be obtained. Taccani et al [37] modelled a HTPEMFC-CHP system considering the degradation of the stack in order to evaluate the system performance over one year of operation. The system's performance in terms of electrical and thermal energy production, energy savings, and import/export of electricity from/to the grid was evaluated for four different configurations with and without battery storage.…”
Section: Htpemfc-chpmentioning
confidence: 99%
“…Due to their easy scale‐up from serving individual homes to large office blocks and industrial complexes, stationary combined heat and power production based on fuel cells (FC‐CHP) is considered as the largest and most established market for fuel cells in near future 1 . The FC‐CHP, which in addition to electricity also provides heat with very high efficiency and low emissions, is a promising technology especially at small scale power production, which is typical for domestic applications 2,3 . Many researchers have paid attention to the FC‐CHP systems in recent years 1–21 …”
Section: Introductionmentioning
confidence: 99%